Legal Certainty in the Transfer of Land Rights Based on Deed of Transfer Under Private Hand Legalized by a Notary - I Ketut Sugiartha; Ni Luh Made Mahendrawati (Warmadewa Press, 2025)
The role of notaries as public officials authorized to prepare authentic deeds is increasingly challenged by the rising complexity of financial crimes such as money laundering. While Indonesian regulations obligate notaries to implement the Know Your Customer principle (Prinsip Mengenali Pengguna Jasa/PMPJ), a normative gap exists in the Law on Notary Office (UUJN), particularly in Article 38, which does not authorize notaries to actively verify the legal identity or intentions of their clients. This discrepancy between regulatory obligation and statutory limitation creates legal uncertainty and exposes notaries to potential criminal liability. Previous studies have focused on compliance issues and ethical dilemmas faced by notaries but lack a comprehensive legal protection framework. This study aims to analyze the normative position of notaries in implementing PMPJ and to formulate an ideal legal protection model. The research employs a normative juridical method with statutory, conceptual, and case approaches, supported by qualitative-deductive analysis. The findings reveal that without the authority to verify client data beyond formal documents, notaries are vulnerable to misuse in money laundering schemes. The study proposes a legal reform model comprising: (1) revision of the UUJN to authorize controlled verification; (2) limited legal immunity for compliant notaries; and (3) integration of technological tools such as digital identity authentication. This work advances the current state of knowledge by highlighting the urgent need for harmonization between notarial duties and anti-money laundering mandates, thereby ensuring both legal certainty and protection for notaries within Indonesia’s evolving legal system.